Pengaruh Leaflet terhadap Motivasi Pengendalian Hipertensi Metode Pretest-Posttest di Puskesmas Sokaraja II dan Sumbang II - Risky Devy Lupitasari; Resy Setem; Ruth Gratia Dwi P; Sesilia Tiara Yuvita; Siti Setianingsih (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Hypertension is one of the non-communicable diseases that remains a major public health problem due to its substantial contribution to morbidity and mortality associated with cardiovascular complications. Effective health education is essential to enhance patients' motivation for hypertension control. This study aimed to analyze the effect of leaflet-based health education on hypertension control motivation among participants of the Chronic Disease Management Program (PROLANIS) at Sokaraja II and Sumbang II Primary Health Centers, Banyumas Regency. This study employed a quantitative approach with a pre-experimental one-group pretest–posttest design. A total of 72 respondents were selected using a random sampling technique. Data were collected using a hypertension control motivation questionnaire administered before (pretest) and after (posttest) the educational intervention using leaflet media. Data were analyzed using univariate analysis to describe respondents' characteristics and motivation levels, while bivariate analysis was performed using the Wilcoxon signed-rank test with a significance level of p<0.05. The results showed an increase in the proportion of respondents with good motivation at Sokaraja II Primary Health Center from 25.00% to 63.89% and at Sumbang II Primary Health Center from 30.56% to 72.22%, accompanied by a decrease in the proportion of respondents with poor motivation. The Wilcoxon signed-rank test demonstrated a statistically significant difference between the pretest and posttest scores (p<0.05). In conclusion, leaflet-based health education was effective in improving hypertension control motivation among PROLANIS participants. Leaflets may serve as an effective health education strategy to support hypertension control in primary healthcare settings.